Diabetes mellitus burden among people living with HIV from the Asia‐Pacific region. Issue 1 (29th January 2019) - Han, Win M; Jiamsakul, Awachana; Kiertiburanakul, Sasisopin; Ng, Oon T; Sim, Benedict LH; Sun, Ly P; Van Nguyen, Kinh; Choi, Jun Y; Lee, Man P; Wong, Wing W; Kamarulzaman, Adeeba; Kumarasamy, Nagalingeswaran; et al.
Abstract: Introduction: Comorbidities including diabetes mellitus (DM) among people living with HIV (PLHIV) are of increasing clinical concerns in combination antiretroviral therapy (cART) era. We aimed to determine the incidence and risk factors of new‐onset DM among PLHIV in Asian settings. Methods: PLHIV from a regional observational cohort without DM prior to antiretroviral therapy (ART) initiation were included in the analysis. DM was defined as having a fasting blood glucose ≥126 mg/dL, glycated haemoglobin ≥6.5%, a two‐hour plasma glucose ≥200 mg/dL, or a random plasma glucose ≥200 mg/dL. A Cox regression model, stratified by site, was used to identify risk factors associated with DM. Results and discussion: Of the 1927 participants included, 127 were diagnosed with DM after ART initiation. Median follow‐up time from ART initiation to DM diagnosis was 5.9 years (interquartile range (IQR): 2.8 to 8.9 years). The crude incidence rate of DM was 1.08 per 100 person‐years (100 PYS), 95% confidence interval (CI) (0.9 to 1.3). In the multivariate analysis, later years of follow‐up (2011 to 2013: HR = 2.34, 95% CI 1.14 to 4.79, p  = 0.02; and 2014 to 2017: HR = 7.20, 95% CI 3.27 to 15.87, p  < 0.001) compared to <2010, older age (41 to 50 years: HR = 2.46, 95% CI 1.39 to 4.36, p  = 0.002; and >50 years: HR = 4.19, 95% CI 2.12 to 8.28, p  < 0.001) compared to <30 years, body mass index (BMI) >30 kg/m 2 (HR = 4.3, 95% CI 1.53 to 12.09, p  = 0.006) compared to BMI <18.5 kg/m 2, and high blood pressure (HR = 2.05, 95% CI 1.16 to 3.63, p  = 0.013) compared to those without high blood pressure, were associated with developing DM. The hazard was reduced for females (HR = 0.47, 95% CI 0.28 to 0.80, p  = 0.006). Conclusions: Type 2 DM in HIV‐infected Asians was associated with later years of follow‐up, high blood pressure, obesity and older age. This highlights the importance of monitoring and routine screening for non‐communicable diseases including DM as PLHIV age.